Study to compare the effect of casirivimab and imdevimab, remdesivir, and favipiravir on progression and multi-organ function of hospitalized COVID-19 patients - Hegazy Sahar K.; Tharwat Samar; Hassan Ahmed H. (Open Medicine, 2023)
Coronavirus disease 2019 (COVID-19) caused a progress in research to find a solution to this pandemic. Also, various advances in pharmacotherapy against COVID-19 have emerged. Regarding antiviral therapy, casirivimab and imdevimab are antibodies combination against COVID-19. Standard antiviral therapy against COVID-19 includes remdesivir and favipiravir. The objectives were to compare progression and multi-organ function of hospitalized COVID-19 patients between these three antiviral groups. 265 COVID-19 hospitalized patients were included in this study and were divided into 3 groups (1:2:2), respectively, Group (A): casirivimab and imdevimab, group (B): remdesivir, and group (C): favipiravir. The design of the study is a single blind non-randomized controlled trial. This study is a phase IV clinical trial (post-marketing study). The duration of the study was about 6 months after receiving the ethical approval. Casirivimab and imdevimab achieved less case progression as presented by lower World Health Organization scale (P < 0.05 in comparing group A with B and C) and better multi-organ functions as presented by lower Sequential Organ Function Assessment score (P < 0.05 in comparing group A with B and C) than remdesivir and favipiravir. From all these results, it is concluded that Group A (casirivimab and imdevimab) produces better outcomes than B (remdesivir) and C (favipiravir) intervention groups.